1996
DOI: 10.1111/j.1399-6576.1996.tb05579.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral autoregulation is impaired in patients resuscitated after cardiac arrest

Abstract: Assuming that the cerebral metabolic rate of oxygen does not change during the interventions in MAP, the changes of CBFI and SjvO2 seen after the decrease or increase in MAP indicate that cerebral autoregulation was impaired in these resuscitated patients. The degree of the impairment of cerebral autoregulation may be secondary to the degree of brain injury caused by the cerebral ischemia accompanying cardiac arrest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(59 citation statements)
references
References 10 publications
0
57
0
2
Order By: Relevance
“…17,27,28 Little human research exists regarding the effect of global anoxia on autoregulation. 4,20,[29][30][31][32][33][34][35][36][37] Animal models have shown a loss of cerebral vascular resistance in the postanoxic state resulting in uncontrolled hyperperfusion. [38][39][40][41][42] Cerebral blood volume has been shown to increase with loss of autoregulation secondary to ischemia, but no large studies have demonstrated a similar relationship for CBF.…”
Section: Resultsmentioning
confidence: 99%
“…17,27,28 Little human research exists regarding the effect of global anoxia on autoregulation. 4,20,[29][30][31][32][33][34][35][36][37] Animal models have shown a loss of cerebral vascular resistance in the postanoxic state resulting in uncontrolled hyperperfusion. [38][39][40][41][42] Cerebral blood volume has been shown to increase with loss of autoregulation secondary to ischemia, but no large studies have demonstrated a similar relationship for CBF.…”
Section: Resultsmentioning
confidence: 99%
“…47,48 These high initial perfusion pressures can theoretically minimize impaired reflow. 49 Yet, hyperemic reperfusion can potentially exacerbate brain edema and reperfusion injury.…”
Section: Post-cardiac Arrest Brain Injurymentioning
confidence: 99%
“…During the subacute period, cerebral perfusion varies with CPP instead of being linked to neuronal activity. 47,48 In humans, in the first 24 to 48 hours after resuscitation from cardiac arrest, increased cerebral vascular resistance, decreased CBF, decreased cerebral metabolic rate of oxygen consumption (CMRO 2 ), and decreased glucose consumption are present. [53][54][55][56] Although the results of animal studies are contradictory in terms of the coupling of CBF and CMRO 2 during this period, 57,58 human data indicate that global CBF is adequate to meet oxidative metabolic demands.…”
Section: Post-cardiac Arrest Brain Injurymentioning
confidence: 99%
“…Nach asphyktischem Kreislaufstillstand kann nach ROSC vorübergehend ein Hirnödem auf-treten; dies ist aber selten mit klinisch relevanten Hirndruckanstiegen verbunden [672,673]. Die Autoregulation des zerebalen Blutflusses bleibt einige Zeit nach dem Kreislaufstillstand gestört, d. h., dass die Hirnperfusion vom zerebralen Perfusionsdruck und nicht von der Neuronenaktivität abhängt [674,675] [686], konnte eine zweite Studie derselben Arbeitsgruppe bei internistischen Intensivpatienten keinen Überle-bensvorteil aufgrund enger Blutzuckereinstellung nachweisen [687]. In einer randomisierten Studie mit Patienten nach präklinischem Kreislaufstillstand und initialem VF bewirkte eine strikte Blutzuckereinstellung (4-6 mmol/l, 72-108 mg/ dl) keinen Überlebensvorteil im Vergleich zu einer moderaten Blutzuckereinstellung (6-8 mmol/l , 108-144 mg/dl), wobei es in der Gruppe mit strikter Einstellung häu-figer zu hypoglykämischen Episoden kam [688].…”
Section: Behinderung (Optimierung Der Neurologischen Erholung) Zerebrunclassified